Study of the Reaction Mechanism in Hydrogen Production Using Metal-Free Schiff Base as a Catalyst - Aguirre-Quintana, M; Aguirre-Quintana, M (Elsevier B.V., 2023)
Understanding the hydrogen evolution reaction and its mechanism is crucial for numerous practical applications in the realm of green energy. The development and discovery of new technologies or alternatives hold great significance in generating hydrogen at a low cost. In this study, we propose a novel catalyst, N, N -bis(2-hydroxy-1-naphthaldehyde)-o-phenylenediamine ([naph]2-o-ph), which is a Schiff base, for hydrogen production. The novelty lies in utilizing the organic Schiff base system and the proposed mechanism for hydrogen evolution, involving protonation and electron exchange on the Schiff base. Both experimental and theoretical results highlight the high capability of the Schiff base in generating hydrogen, providing valuable insights for potential applications in water electrolysis. © 2023 Elsevier B.V.